Symmetry and uniqueness of positive solutions for a Neumann boundary value problem - Bensedik, Ahmed; Bouchekif, Mohammed (Applied mathematics letters, 2007)
This work deals with the existence and symmetry of positive solutions for a Neumann boundary value problem. It is a generalization of the work of Pedro J. Torres. The main result is the uniqueness of positive solutions, which is proved by an analytical method, for a given interval of the positive parameter q.
Keywords: Krasnoselskii theorem; Neumann conditions; Green’s function; Symmetry; Uniqueness and positivity of solutions